Zero hunger and malnutrition in the African continent is potentially feasible, if nutrition programs are prioritized politically and scientifically - Hussein, Laila (The North African Journal of Food and Nutrition Research, 2021)
African countries and in particular the Sub Sahara ones contribute to the largest proportion of the global burden of poverty and associated diet related diseases in all its forms, including micronutrient malnutrition. Malnutrition rates remain alarming: and stunting an indicator of chronic malnutrition is declining too slowly The main objectives of the present article is to focus on 1- the current food supply and nutritional status among the vulnerable young population in African countries 2- Insight on the efforts towards reaching the global goal (2) for ending hunger within the context of the SDS2030. The methodology included urgent short- and medium term interventions priorities programs implemented by foreign aids and international organizations for the management of severe and moderate malnutrition among African children. Details on the composition of the so-called ready to use foods used for treating malnourished children is presented. The outcomes of such programs with all their positives and negatives were put together as lessons to be learned and to close the information gap. The cost for treating one single malnourished child by these ready to use foods is in the range between 50 up to 200 US. To make Goal 2 a reality by the year 2030, a number of scientific based sustainable solutions were created and recommended for application. Maximizing the use of local food resources, and minimizing losses by applying the logarithm of linear modeling so that nutritious recipes can be formulated at lowest cost. Capacity building of junior African academics and increased investments in research focusing on diet quality for optimizing the formulation of recipes for feeding infants and children. Strengthening scientific collaboration and exchange of visits and experiences between scientists from the 54 African countries. The establishment of an African Consortium with experts in the diverse areas of food systems to work together more effectively under the umbrella of the African union.